Efficacy of Xpert MTB/RIF Assay in the Diagnosis of Smear Negative HIV Seropositive Pulmonary Tuberculosis Patients - Bansal, Reetika; Arora, Shilpa; Jindal, Neerja; Bansal, Renu; Sharma, Vishal (Annals of Pathology and Laboratory Medicine, 2019)
Background: Tuberculosis (TB) is the most common presenting illness and leading cause of death among people living with HIV(PLHIV). Diagnosis of TB among PLHIV is challenging as false negative results are common with direct microscopy (DM) and culture takes long time. WHO (2013) recommended Xpert MTB/RIF assay as an initial test for diagnosis of TB in PLHIV. Methods: The present study was conducted on 142 HIV seropositive patients who were clinically suspected to have TB. The sputum specimens obtained from these patients were divided into two parts; one was processed by DM and the other was used for Xpert MTB/RIF assay. Result: Of the 142 HIV seropositive patients, 90(63.3%) were in the age group of 15-40 years and majority 91(64.08%) were males. Out of 142 sputum specimens collected from these patients, only 5(3.52%) were positive by DM and 31(21.83%) by Xpert MTB/RIF assay. Statistically the difference between the two was significant (p value <0.005). Xpert MTB/RIF assay showed rifampicin resistant in 2(6.45%) specimen. Of the 137 smear negative specimens, Xpert MTB/RIF assay gave positive result in 27 (19.70%). Thus, the sensitivity, specificity, PPV, NPV of the Xpert MTB/RIF assay in comparison to DM was 80% (95%CI=37.6- 96.4), 80.29% (95%CI=72.8-86.1), 12.90% (95%CI=4.21-30.76), 99.09%(95%CI=94.3-99.9) respectively. Conclusion: Xpert MTB/RIF assay was found to be a sensitive, specific and rapid method for diagnosis of TB and rifampicin resistance in smear negative PLHIV. It’s availability as an initial diagnostic test in PLHIV could significantly reduce the delay in initiation of treatment and prevent the transmission of the disease.